Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

La question du consentement sexuel: entre liberté individuelle et dignité humaine - Simard, D. (Sexologies, 2015)
En matière sexuelle, le consentement est une notion devenue primordiale. Elle permet sur le plan juridique, notamment, de distinguer ce qui ne relève pas du viol et ce qui en relève. C’est toutefois une notion aux contours mal définis, qui donne lieu à des controverses, particulièrement sur la question de la prostitution et sur celle du sadomasochisme pour ce qui concerne l’éthique de la sexualité. Cet article a pour objectif de tenter d’éclairer les termes du débat. Il interroge d’abord les fondements du consentement sexuel, en analysant les différences ou les confusions conceptuelles entre le désir et la volonté, tout d’abord à partir de la lecture des philosophes du XVII e siècle René Descartes et Baruch Spinoza, qui s’opposent sur la place du désir relativement à la raison chez l’être humain, et ensuite du psychanalyste Sigmund Freud, qui introduit l’idée de désir inconscient. L’article montre ensuite comment l’impossibilité d’une liberté absolue, et donc d’un consentement dégagé de toute contrainte, peut conduire certaines organisations féministes à mettre en question le consentement individuel même clairement formulé, et à lui opposer la notion de dignité humaine en un sens transcendant, inspirée du philosophe allemand du XVIII e siècle Emmanuel Kant. Cette notion est interrogée et étudiée dans les cas de la prostitution et du sadomasochisme. L’analyse conceptuelle conduit à mettre en évidence le caractère métaphysique tant de l’approche individualiste du consentement que de l’approche d’inspiration kantienne de la dignité humaine.
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; corps; cours; discipline; europe; phi2030; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques